The relationship between selenium retention and fine particles removal during coal combustion. (1st April 2020) - Ma, Tongtong; Huang, Yongda; Deng, Shuang; Fu, Biao; Luo, Guangqian; Wang, Jinggang; Hu, Hongyun; Yuan, Chungang; Yao, Hong
Highlights: Se is higher in the rear ESP ash than in front hopper due to Se enrichment in PM2.5. Se (IV) was the dominant chemical species (＞90%) including SeO2 (s) and selenites. Fe may lead to the Se (VI) formation in coarse fly ash. Fabric filter (FF) can relatively capture more selenium (＞60%) through physical condensation at lower temperature. Abstract: Selenium (Se) mostly evaporates during coal combustion and the transformation of gaseous Se towards particulate forms favors its emission control by dust purification devices. For better control of Se emission, the present study explored the relationship between Se retention and fine particles removal during coal burning. The distribution of Se within the dust collection system followed a non-linear increasing trends i.e., the concentration of Se peaked in the last ESP hoppers and was significantly enriched in PM2.5 . Further study demonstrated that the conversion pathway of SeO2 (g) to the particulate Se is related to the types of ash collection devices (ESP vs FF). More Se (g) condensed to SeO2 in FF ash (greater than 60%) whereas the chemisorption dominated the formation of Se-enriched ESP ash (greater than 65%). With selenites (IV) being the dominant chemical forms in fly ashes, selenate (VI) was found to be enriched in the coarse ESP ash which may be formed through the capture and oxidation by Fe-oxides. Compared with arsenic from the same power plants, more gaseous selenium penetrated the ash collection devices. Se tended to be more enriched in fine particles and can be more captured by fly ash through physisorption relative to As. The results suggested that the contribution of each ash collection devices for Se removal should consider not only the unique enrichment behavior of Se towards the rear ESP hoppers and fine particles (PM2.5 ), but also using fabric filter or other techniques for strengthening the process of condensation of SeO2 (g).